CSR Program PT. SHELL Indonesia CSR - Reyhan, Achmad; Rudito, Bambang (Journal of Business and Management, 2012)
Corporate Social Responsibility is the continuing commitment by business to behave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as of the local community and society at large. By these means, the CSR is a program that will help government to support the society needs in order to make a mature society. PT Shell Indonesia is engaged in the oil industry which has a program to get recognition and can be assessed positively by the community, especially those located in the vicinity of the operating company. PT Shell Indonesia conducts programs that not only are the government responsibility, but also a social responsibility to this company, this program is called CSR. CSR aims to increase people's access to achieve social, economic, and culture aspects better when compared with before any construction activities took place. So that local communities can assess any positive value in the presence of Shell Companies in Indonesia. Purpose: To discuss and describe the programs and activity of PT Shell Indonesia’s CSR in Indonesia. This demonstrated through efforts is taken in order to enhance the development of Indonesian society, especially around the industrial area. Design/methodology/approach: The method is using a research that conducted qualitative descriptive research method and qualitative data collection techniques. The purpose of descriptive method is to create a description of a picture or painting in systematic, factual and accurate information on the facts, the properties of the relationship between the phenomena investigated. The purpose of this descriptive method is to get an idea about the social, economic, cultural and political society that affect the implementation of Community Development which can ultimately affect the implementation of Community Development. Research limitations/implications: In the line of the condition in Indonesia, the needs of our people are greater than it looks. The real problem is the basic education, many people in Indonesia still don’t have a chance to get elementary school and junior high school, and those two are the basic component in building the mature and more advance society. As we can see in appendix for the education indicator, the people need a helping hand besides the government itself, this where the CSR program can penetrate even greater. I will give my opinion and suggestion for CSR program, not only for PT. Shell Indonesia, but also for every company in Indonesia that have a willingness to contribute in basic needs of people advancement.Choose the partnership program with elementary and junior high school program. This partnership can be in form of real free tuition fee for student to get education from school without paying any of the school material. The CSR program can spend their fund in the bonus wages of the teacher, the book that student needs, the improvement of the building school. Open the public school in the name of the company. This way can also be more effective as the 1st one because the check and balance of the school program can be monitored by the CSR team itself. This way the student of these schools can live just to think how to get an education that he/she needs, not the cost of exam fee, or training bulletin fee, uniform fee, etc. Social implications: The impact to the society especially to the company that have to perform CSR is to deliver the good insight to them to decide what is the best and the most useful CSR program to be implemented for the society of Indonesia. Originality/value: The value of this paper is targeted especially to the company in Indonesia to perform better CSR.Keywords: CSR, SHELLCategory: Knowledge Management; Human Capital Management